Marketing Strategy for Air Force Central Hospital Dr. Suhardi Hardjolukito Yogyakarta: A SWOT Analysis - Yochanan, Elisha; Wibowo, Markus; W, Dr dr F Sukma (International Journal of Health Sciences, 2024)
The study titled "Marketing Strategy for Air Force Central Hospital Dr. Suhardi Hardjolukito Yogyakarta: A SWOT Analysis" aimed to develop a comprehensive marketing strategy framework for the hospital management to enhance service delivery and patient satisfaction. Utilizing primary and secondary data sources through interviews, questionnaires, and literature review, the SWOT analysis identified the hospital's strengths, weaknesses, opportunities, and threats, leading to strategic recommendations. The study concluded that with effective marketing strategies, such as competitive pricing, strategic communication, and service excellence, the hospital could significantly improve its market position and patient intake.